EFFECT OF RADIATION PRESSURE ON DYNAMICAL STRUCTURES IN THE CIRCULAR ROBE’S R3BP WITH VARIABLE MASSES (FUDMA JOURNAL OF SCIENCES, 2024)
The paper investigates effect of radiation pressure on dynamical structures in the Robe’s restricted three-body problem (R3BP) with variable masses. The non-autonomous equations of the dynamical system are obtained and transformed to the autonomized equations with constant coefficients under the condition that there is no fluid inside the first primary. Next, the equilibrium points (EPs) of the autonomized system are explored and the stability is investigated analytically and numerically. It is observed that the axial and non-collinear EPs can be stable and unstable depending on the values of the mass parameter, radiation pressure of the second primary and the mass variation parameter. In the case of the axial equilibrium point (EP), the radiation pressure reduces the region of stable motion while the mass variation parameter can have both stabilizing and destabilizing effects.  The stability of the EPs of the non-autonomous equations is analyzed and it is seen that the solutions do not converge, and are unstable EPs. Finally, the ZVCs around the EPs are explored and it is seen that, the radiation pressure of the second primary decreases the region where motion of the satellite around the axial EP, is allowed, while the mass parameter and the parameterdecreases or increases the region where motion of the satellite around the axial EP is allowed, as they are increased or decreased, respectively. In the case of the non-collinear points, the radiation of the second primary increases the region where motion of the satellite is allowed, while an increase in the mass parameter...
Keywords: Robe’s R3BP; Stability; Zero velocity curves; Variable mass; Radiation pressure